2017
DOI: 10.1097/scs.0000000000003850
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Orthognathic Surgery Edema Assessment With and Without Manual Lymphatic Drainage

Abstract: Manual lymphatic drainage was effective in reducing facial measurements in orthognathic surgery postoperatory. When considering patient's pain and swelling perception, no difference was found between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
0
29
0
8
Order By: Relevance
“…Manual lymphatic drainage for the treatment of oedema after maxillofacial surgery does not seem as popular as in other fields of surgery. There are, however, publications that could show its benefit [24][25][26], and one ongoing trial is evaluating its clinical relevance [27]. Two studiesnot included in this review due to the lack of control group in one and the lack of detailed information from a conference abstract in the other-state a benefit of kinesiotape application after penile surgery [28,29], emphasizing the advantageous versatility of the technique that is adaptable to various anatomic regions.…”
Section: The Broader Contextmentioning
confidence: 99%
“…Manual lymphatic drainage for the treatment of oedema after maxillofacial surgery does not seem as popular as in other fields of surgery. There are, however, publications that could show its benefit [24][25][26], and one ongoing trial is evaluating its clinical relevance [27]. Two studiesnot included in this review due to the lack of control group in one and the lack of detailed information from a conference abstract in the other-state a benefit of kinesiotape application after penile surgery [28,29], emphasizing the advantageous versatility of the technique that is adaptable to various anatomic regions.…”
Section: The Broader Contextmentioning
confidence: 99%
“…The MLD had proven efficacy in the postoperative period of third molar extraction, alveolar bone graft, and orthognathic surgery [90][91][92]. In a clinical trial with a split mouth model, third molar extraction was performed by adding MLD on one side only in the postoperative period.…”
Section: Manual Lymphatic Drainage (Mdl)mentioning
confidence: 99%
“…It was also observed that the maximum edema was lower in the patients who received the MLD. Thus, MLD is able to promote the control of edema when applied during its development period and also to accelerate the process of regression of swelling in the postoperative period [91,94].…”
Section: Manual Lymphatic Drainage (Mdl)mentioning
confidence: 99%
See 2 more Smart Citations